Heart Rate Methods Can Be Valid for Estimating Intensity Spectrums of Oxygen Uptake in Field Exercise - Salier Eriksson, Jane; Olsson, Karin S. E.; Rosdahl, Hans; Schantz, Peter (Frontiers in Physiology, 2021)
Purpose: Quantifying intensities of physical activities through measuring oxygen uptake (V̇O2) is of importance for understanding the relation between human movement, health and performance. This can in principle be estimated by the heart rate (HR) method, based on the linear relationship between HR and V̇O2 established in the laboratory. It needs, however, to be explored whether the HR method is valid for estimating spectrums of V̇O2 in field exercises. We hereby initiate such studies using cycle commuting as the form of exercise. Methods: Ten male and ten female commuter cyclists underwent measurements of HR and V̇O2 while performing ergometer cycling in a laboratory and a normal cycle commute in the metropolitan area of Stockholm County, Sweden. Two models of individual HR-V̇O2 relationships were established in the laboratory through regression equations. Model 1 included three submaximal intensities, whereas model 2 also involved a maximal intensity. The HR-V̇O2 regression equations of the two models were then used to estimate V̇O2 at six positions of field HR: five quintile means and the mean of the whole commute. The measured and estimated V̇O2 were compared for both models. Results: The measured quintile range during commuting cycling was about 45-80% of V̇O2max. Overall, there was a high resemblance between the measured and estimated V̇O2, without any significant absolute differences in either males or females (range of all differences: -0.03 - 0.20 L·min-1). Simultaneously, rather large individual differences were noted. Conclusion: The present HR methods are valid at group level for estimating V̇O2 of cycle commuting characterized by a relatively wide spectrum of exercise intensities. To further the understanding of the external validity of the HR method, there is a need for studying other forms of field exercises.